Implementasi Metode Maqashid Syariah Imam Al Syathibi pada Praktik Perbankan Syariah di Indonesia - Lasri Nijal; Putri Apria Ningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Only with the Maqashid Syari'ah approach that Islamic banking and financial products can develop well and can respond to the progress of business that continues to change rapidly. Imam Al-Syatibi was dubbed the father of Maqashid Sharia because of the results of his work which had systematized Maqashid al-Shari'ah into a new methodology that produced ijtihady jurisprudence or Maqashidy fiqh. In the context of Sharia business practices, the achievement of Maqashids Shariah can be measured through the achievement of goals in the form of individual education or knowledge, creation of justice and achievement of public interests. Sharia banks must ensure fair transactions in all business activities, including products, prices and the time period in the contract and its conditions. Islamic banks must also ensure that all business ventures that are free from negative elements can cause injustice, such as usury (including interest), fraud, corruption, etc. Keywords: Maqashid, Al Syathibi, Islamic Banking